Supportive Self-Management Program for People With Chronic Headaches and Migraine: A Randomized Controlled Trial and Economic Evaluation. (28th March 2023) - Underwood, Martin; Achana, Felix; Carnes, Dawn; Eldridge, Sandra; Ellard, David R.; Griffiths, Frances; Haywood, Kirstie; Hee, Siew Wan; Higgins, Helen; Mistry, Dipesh; Mistry, Hema; Newton, Sian; et al.
Abstract : Background and Objectives: Chronic headache disorders are a major cause of pain and disability. Education and supportive self-management approaches could reduce the burden of headache disability. We tested the effectiveness of a group educational and supportive self-management program for people living with chronic headaches. Methods: This was a pragmatic randomized controlled trial. Participants were aged 18 years or older with chronic migraine or chronic tension–type headache, with or without medication overuse headache. We primarily recruited from general practices. Participants were assigned to either a 2-day group education and self-management program, a one-to-one nurse interview, and telephone support or to usual care plus relaxation material. The primary outcome was headache related-quality of life using the Headache Impact Test (HIT)-6 at 12 months. The primary analysis used intention-to-treat principles for participants with migraine and both baseline and 12-month HIT-6 data. Results: Between April 2017 and March 2019, we randomized 736 participants. Because only 9 participants just had tension-type headache, our main analyses were on the 727 participants with migraine. Of them, 376 were allocated to the self-management intervention and 351 to usual care. Data from 586 (81%) participants were analyzed for primary outcome. There was no between-group difference in HIT-6 (adjusted mean difference = −0.3, 95% CI −1.23 to 0.67) or headache days (0.9, 95% CI −0.29 to 2.05) at 12 months. The Chronic Headache Education and Self-management Study intervention generated incremental adjusted costs of £268 (95% CI, £176–£377) (USD383 [95% CI USD252–USD539]) and incremental adjusted quality-adjusted life years (QALYs) of 0.031 (95% CI −0.005 to 0.063). The incremental cost-effectiveness ratio was £8, 617 (USD12, 322) per QALY gained. Discussion: These findings conclusively show a lack of benefit for quality of life or monthly headache days from a brief group education and supportive self-management program for people living with chronic migraine or chronic tension–type headache with episodic migraine. Trial Registration Information: Registered on the International Standard Randomized Controlled Trial Number registry, ISRCTN79708100 16th December 2015 doi.org/10.1186/ISRCTN79708100 . The first enrollment was April 24, 2017. Classification of Evidence: This study provides Class III evidence that a brief group education and self-management program does not increase the probability of improvement in headache-related quality of life in people with chronic migraine.